The Size Effect on the Temperature Dependence of the Resistivity of Metal Films - L.V. Odnodvorets (Журнал нано- та електронної фізики)
The analysis of the temperature dependences of the electrical conductivity of thin metal films is per-formed. It is shown that the size dependence of the effective parameter of the electron-phonon interaction is connected with amplification of high-temperature electron-phonon interaction at the decrease in the film thickness which appears as a result of the shift of the phonon spectrum to higher frequencies. We have found that the slope of the experimental temperature dependences of the resistance for Pd, Pt, and Sc films, as in the case of Mo, Cr, Ag, Au, and PdAu films, according to the data of other authors, increases with the decrease in the thickness. As the film thickness decreases the average phonon energy increases that leads to the increase in the efficiency of the electron-phonon scattering and, finally, to the increase in the resistivity.